Simulation of the impact of firebrands on the process of the wood layer ignition - Matvienko, Oleg V.; Kasymov, Denis P.; Loboda, Egor L.; Lutsenko, Anastasia V.; Daneyko, Olga I. (Fire)
In this study, a theoretical formulation of the ignition and combustion of the wood layer by burning and smoldering firebrands has been considered. The effect of the firebrands’ length, distances between firebrands and their geometrical parameters on the heat exchange with the wood layer and the ignition process were analyzed. With a decrease in firebrand size, ignition of wood is possible with a decrease in the distance between the firebrands. With an increase in firebrand size at the same distance between them, the ignition regime becomes possible albeit with a longer delay time dt. With a decrease in the distance between the firebrands, the ignition of wood is possible with an increase in dt. As a result of mathematical modeling of the process, the following processes are noted: the heat stored in firebrands of small sizes is insufficient to initiate the ignition process; the temperature in the wood layer, due to conductive heat exchange, slightly increases at first, before beginning to decrease as a result of heat exchange with the surrounding air and the wood layer; intensive heat exchange with the environment of small size firebrands leads to the end of firebrand smoldering and its cooling; and, if the firebrand size reaches a critical value, then the pyrolysis process begins in the area adjacent to it.